Community structure and biomass of larval euphausiids and postlarval mysids in relation to anomalous warming events during a weekly time series (2014–2017) at Cabo Pulmo National Park, Mexico. (November 2022) - Ventura-Domínguez, Phalom D.; Gómez-Gutiérrez, Jaime; De Silva-Dávila, Roxana; González-Rodríguez, Eduardo; Sánchez-Uvera, Arturo R.; Silveyra-Bustamante, Ángel A.; Trasviña-Castro, Armando; Aburto-Oropeza, Octavio; Sánchez, Carlos
Highlights: Marine heatwaves 2014 (Jan–Aug) and El Niño (May 2015–May 2016) caused anomalously warm temperatures at the south Gulf of California. Eight euphausiid (98% larvae) and five mysid (mostly juveniles and adults) species, mostly of tropical-oceanic affinity, were collected between 2014 and 2017. Nyctiphanes simplex dominated during the cold seasons and Euphausia distinguenda dominated during the warm seasons with small interannual changes. The demersal neritic species, Mysidium rickettsi, accounted for 99.98% of total mysid abundance. Haplostylus bengalensis is a new record in the Mexican Pacific. Euphausiid abundance and biomass declined during the MHW 2014 and El Niño 2015–2016; but E. distinguenda and M. rickettsi were more abundant during El Niño 2015–2016. Abstract: Euphausiids and mysids are important components of pelagic ecosystems due to their high abundance and tendency to form dense aggregations, swarms, and schools, which concentrate biomass that attracts visual predators. Species richness, abundance, and carbon biomass of euphausiids and mysids were investigated from a weekly daytime surface zooplankton time series from 2014 to 2017, in relation to 15 environmental variables at Cabo Pulmo National Park (CPNP, 23°27′ N, 109°25′ W), Mexico. A marine heatwave (MHW; January–August 2014) and El Niño 2015–2016 (May 2015–May 2016) caused anomalously warm temperatures in relation to the 2002–2018 temperature time series. We tested the hypotheses that CPNP is dominated by a tropical euphausiid and mysid species assemblage and that abundance of both taxonomic groups decreased during the MHW 2014 and El Niño 2015–2016. Euphausiids (7.9 ind. m −3 ) had a higher mean abundance than mysids (3.4 ind. m −3 ). Eight euphausiid species, mostly of tropical-oceanic affinity, were collected (98 % larvae). Nyctiphanes simplex decreased and Euphausia distinguenda and Stylocheiron carinatum increased in abundance during El Niño 2015–2016. Five mysid species were collected (juveniles and adults). Mysidium rickettsi alone accounted for 99.98 % of total mysid abundance. Although the euphausiids collected were mainly larval stages, due to sampling in shallow coastal waters during the day, they contributed more biomass than juvenile and adult M. rickettsi in the pelagic habitat, though the abundance of this mysid in its epibenthonic habitat was likely underestimated. A canonical correspondence analysis of euphausiid and mysid abundance as a function of 10 environmental variables explained 77.4 % of the total variability, showing greater seasonal (warm vs cold) than interannual changes. The best correlated environmental variables with euphausiid and M. rickettsi abundance were net primary production (−0.419), zooplankton biovolume (0.3177) and the MEI.v2 (−0.278). We concluded that the most evident changes in community structure and abundance were seasonal (e.g. N. simplex dominated during the cold season while E. distinguenda dominated during the warm season) rather than interannual. Moreover, the abundance and biomass of euphausiids decreased during the MHW 2014 and El Niño 2015–2016; paradoxically the highest abundance and biomass of E. distinguenda and the mysid M. rickettsi occurred during El Niño 2015–2016. This implies higher available biomass for benthonic and nektonic predators in this neritic tropical reef ecosystem, contrasting with decreased abundance of euphausiids observed along the west coast of the Baja California Peninsula during this period.